Frightened by the eagle; Recording songs and music from the Island of Siberut, Mentawai Islands - Persoon, Gerard A.; Schefold, Reimar (Wacana, Journal of the Humanities of Indonesia, 2017)
Singing is the most important element of the traditional music culture on Siberut, the largest of the Mentawai Islands (West Sumatra, Indonesia). There are various types of songs on the island. Some of them are related to the world of spirits and ancestors. These are mainly sung by shamans during healing ceremonies and rituals. Other songs are made up by men and women during their daily activities, when they are fishing out at sea or when they take a rest from collecting forest products. Various animals (birds, primates, reptiles) or natural forces (wind, thunder) provide inspiration for lyrics and melodies, as do special events, like the arrival of a logging company on the island). In this article, we discuss the process of recording the songs and other types of music of the island and the production of two CDs and the reactions of the singers and the community to the presentation of the CDs. In a context of decades of suppression of various aspects of the traditional culture (religion, tattoo, loincloth) documentation of a form of intangible culture and its positive appreciation can generate a sense of pride among a local community. In addition, we have added an extensive appendix to this article containing the lyrics of a number of songs in both the local language as well as in translation. It allows readers to get an idea of the poetic nature of the song literature of the Mentawaians.